Authoritarianism and corporatism in Europe and Latin America
1 online resource.
Keywords: "What drove the horizontal spread of authoritarianism and corporatism between Europe and Latin America in the twentieth century? What processes of transnational diffusion were in motion and from where to where? In what type of 'critical junctures' were they adopted and why did corporatism largely transcend the cultural background of its origins? What was the role of Intellectual-politicians in the process? This book will tackle these issues by adopting a transnational and comparative research design encompassing a wide range of countries"--